2021
DOI: 10.1002/anie.202110445
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Role of a Short‐Chain Dehydrogenase/Reductase Family Protein in Type II Polyketide Biosynthesis

Abstract: We investigated the biosynthetic pathway of type II polyketide murayaquinone.T he murayaquinone biosynthetic cluster contains genes for three putative short-chain dehydrogenase/reductase family enzymes including MrqFa nd MrqH with knownf unctions and MrqMw ith unclear function. We report the functional characterization of MrqMf or its role in murayaquinone biosynthesis.O ur gene deletion experiment and structural elucidation of the accumulated intermediates revealed that MrqM is related with the second polyket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…ActIV was characterized as a bifunctional cyclase-thioesterase via in vitro reconstitution of actinorhodin biosynthesis pathway, and it was also demonstrated with TE activity towards a model substrate of type II PKS, anthraquinone-2carboxylic acid-N-acetylcysteamine [14]. MrqD was suggested to function as a dedicated product releasing TE in murayaquinone biosynthesis based on the interpretations of gene deletion and sitedirected mutagenetic analysis [15]. With the information, we speculate that NftF 1 played the role of transacting TE to release the precursor chain of compound 3, and a subsequent hydroxylation on 3 provided 4.…”
Section: Exploration Of the Nfte-mediate Polyketide Aromatic Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…ActIV was characterized as a bifunctional cyclase-thioesterase via in vitro reconstitution of actinorhodin biosynthesis pathway, and it was also demonstrated with TE activity towards a model substrate of type II PKS, anthraquinone-2carboxylic acid-N-acetylcysteamine [14]. MrqD was suggested to function as a dedicated product releasing TE in murayaquinone biosynthesis based on the interpretations of gene deletion and sitedirected mutagenetic analysis [15]. With the information, we speculate that NftF 1 played the role of transacting TE to release the precursor chain of compound 3, and a subsequent hydroxylation on 3 provided 4.…”
Section: Exploration Of the Nfte-mediate Polyketide Aromatic Cyclizationmentioning
confidence: 99%
“…However, the MBL fold TEs were never reported in the type I PKSs that conventionally o oad chain by using an /ß hydrolase-type TE domain integrated at the C-terminus of PKS assembly line via thioester hydrolysis or O-C macrocyclization [13]. So far, only two cases of MBL fold hydrolases were experimentally investigated in the biosynthesis of type II polyketides actinorhodin and murayaquinone, in which ActIV and MrqD were characterized as MBL fold TEs for chain release based on genetic mutations and the in vitro analysis with an arti cial substrate [14,15]. Interestingly, these cognate genes appear popular in type II PKS BGCs, and they are usually annotated as ring cyclase/aromatase such as RslC2, AlnR and Ssfy2 derived from the biosynthesis of rishirilides, alnumycin and tetracycline SF2575 [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that CLF phylogeny more tightly correlates with the number of polyketide building block employed rather than the total carbon number. , During polyketide assembly the full-length reactive nascent poly-β-keto chain is often converted to the defined polycyclic skeleton as a result of a combination of ketoreductases, cyclases, and aromatases . Cyclases/aromatases function in a chaperone-like manner, catalyzing regioselective intramolecular aldol condensations en route to ring formation. , In the absence of cyclases/aromatases, spontaneous intramolecular cyclization of the highly reactive poly-β-keto intermediates can occur, leading to the formation of various shunt products. , …”
mentioning
confidence: 99%
“…Specific to the production of aromatic polyketides, reminiscent here are the studies implicating the participation of NAD(P)(H)-dependent short chain dehydrogenases/reductases in catalyzing or facilitating polyketide cyclization/ aromatization reactions. 37,38 Complementary to in vivo gene manipulation experiments, the total in vitro reconstitution of large modular type I PKSs is now accessible which enables the discovery of new polyketide natural products and polyketide assembly line engineering. 39−41 Here, we employ the total in vitro reconstitution of the type I PKSs to discover a novel post-PKS tailoring enzymatic activity.…”
mentioning
confidence: 99%
“…The discovery of new tailoring enzymes that participate in the construction of polyketide antibiotics has traditionally relied on in vivo gene deletion experiments in native or heterologous hosts, the detection and isolation of biosynthetic intermediates, and assignment of the tailoring enzyme activities by gene complementation and model or native in vitro reactions. Specific to the production of aromatic polyketides, reminiscent here are the studies implicating the participation of NAD­(P)­(H)-dependent short chain dehydrogenases/reductases in catalyzing or facilitating polyketide cyclization/aromatization reactions. , Complementary to in vivo gene manipulation experiments, the total in vitro reconstitution of large modular type I PKSs is now accessible which enables the discovery of new polyketide natural products and polyketide assembly line engineering. Here, we employ the total in vitro reconstitution of the type I PKSs to discover a novel post-PKS tailoring enzymatic activity. We demonstrate that the Plt PKSs themselves produce a biologically inactive alicyclic dihydrophloroglucinol polyketide product, a chemical class of products previously not reported to be produced by type I PKSs.…”
mentioning
confidence: 99%